Comparative analysis of male androgen responsiveness to social environment in birds: The effects of mating system and paternal incubation - Hirschenhauser, Katharina (2003)
Male androgen responses to social challenges have been predicted to vary with mating system, male–male aggressiveness, and the degree of paternal investment in birds (“challenge hypothesis,” Am. Nat. 136 (1990), 829). This study focused on the interspecific predictions of the challenge hypothesis. Comparative methods were used to control for effects of the phylogenetic relatedness among the sampled species. Male androgen data of 84 bird species were collected from literature records on seasonal androgen patterns. From these, the androgen responsiveness (AR) was calculated as described in the original challenge hypothesis (i.e., maximum physiological level/breeding baseline). Scatterplots of AR versus mating strategy, male–male aggressiveness, and the degree of paternal care confirmed the expected interspecific patterns. When phylogenetic analyses were performed among all of the sampled species, the effects of paternal investment disappeared while the AR remained covarying to a high degree with mating system and male–male aggressiveness. Although these mechanisms may be different at the intraspecific level, this suggests that interspecific differences of AR in male birds may have evolved in response to changes of mating strategies, rather than in response to altered paternal duties. However, control for phylogeny among the subsample of 32 passerine species revealed that if any paternal investment contributed to the observed variance in AR, then the change from “no male incubation” to “male shares incubation duties” represented the most effective, whereas the male’s contribution to feeding offspring did not explain the observed variation of AR.